Hunger and Obesity as Symptoms of Non-Sustainable Food Systems and Malnutrition - Gerald Steiner; Bernhard Geissler; Eva S. Schernhammer (Applied Sciences, 2019)
Among the great challenges the world faces are how to ensure food security for its growing population—projected to rise to around 10 billion by 2050—so it can meet their nutritional needs for a healthy life. Current regulations and literature on food security mainly focus on food quantity (i.e., portion sizes), daily calorie intake and methods for increasing food production and too little on food and diet quality and the holistic effects of (mal)nutrition. From a systems perspective, in order to promote innovation policies for more sustainable food systems, food security cannot be viewed independently; rather, it is characterized by the interplay of an extensive network of economic, environmental and social dimensions that should all be taken into account in a comprehensive resilient and sustainable global food system. Here, we highlight one aspect of this vast network that we consider a particular challenge—yet also a great opportunity—for innovative policies geared toward more sustainable food systems: the interplay of hunger and obesity, including resulting policy strategies beyond potential efficiency improvements in farming practices. Future studies need to emphasize the importance of an in-depth understanding of the interdependencies within the global food system and its interrelatedness with societal and natural systems as part of coupled human-environment systems and in the face of continuing population growth and food demand globally. Recommended strategies for achieving sustainable food security systems include innovative educational approaches and stakeholder-driven innovation policies based on mutual learning processes between society, science, industry and policymakers, as well as fostering increased responsibility of all members of society along the agriculture and food value chain.